Targeting Delivery Nanocarriers for (+)-Terrein to Enhance Its Anticancer Effects - Jiang, Yao-Yao (ACS Omega, 2020)
[Image: see text] As a compound from marine fungi, (+)-terrein showed significant anticancer activity. In this study, (+)-terrein was extracted from the marine-derived fungus and showed significant cytotoxicity against cancer cells, especially in A549 cells. To enhance its anticancer effects, redox-responsive nanocarriers based on folic acid-chitosan decorating the mesoporous silica nanoparticles were designed to control (+)-terrein target delivery into cancer cells. (+)-Terrein was loaded in the holes, and folic acid-chitosan worked as a gatekeeper by disulfide linkage controlling (+)-terrein release in the tumor microenvironment. The (+)-terrein drug delivery systems exhibited cytotoxicity toward A549 cells through induction of apoptosis. The apoptosis effect was confirmed by the increase in the expression of cleaved caspase-3, caspase-9, and PARP. Taken together, this work evaluates for the first time the (+)-terrein delivery system and provides a promising nanomedicine platform for (+)-terrein.